2006
DOI: 10.1577/a05-064.1
|View full text |Cite
|
Sign up to set email alerts
|

Use of Luteinizing Hormone Releasing Hormone Analog and Human Chorionic Gonadotropin to Spawn Early‐Egg‐Stage Striped Bass

Abstract: Female striped bass Morone saxatilis with eggs in early stages of development were successfully spawned after being given a priming injection of luteinizing hormone releasing hormone analog followed by a resolving injection of human chorionic gonadotropin (HCG). Over 2 years, 18 of 19 injected fish spawned, producing over 3.5 million viable fry. Egg fertilization rates for all fish that spawned averaged 41%. This procedure, which differs from the traditional spawning method of HCG injection, can increase produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In order to meet hatchery goals, brood fish collection often extends beyond the peak in natural spawning. Brood fish collected outside of peak spawning often produce inferior‐quality sperm or eggs (Yeager 1990; Yeager et al 2006) reducing survival to fry stage. Brood fish collection during this study began before peak spawning activity.…”
Section: Discussionmentioning
confidence: 99%
“…In order to meet hatchery goals, brood fish collection often extends beyond the peak in natural spawning. Brood fish collected outside of peak spawning often produce inferior‐quality sperm or eggs (Yeager 1990; Yeager et al 2006) reducing survival to fry stage. Brood fish collection during this study began before peak spawning activity.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the use of PIM does not improve the GnRHa treatment and the use of GnRHa alone during the last stages of vitellogenesis is enough to induce final oocyte maturation in European sea bass. Yeager (2006) found that LH-RHa given in combination with HCG could advance oocyte maturation and induce spawn female striped bass Morone saxatilis that otherwise would be considered insufficiently mature for induced spawning. Females with eggs in early stages of development were successfully spawned (18 of 19) after being given a priming injection of LH-RHa followed by a resolving injection of human chorionic gonadotropin (HCG).…”
Section: Induced Spawningmentioning
confidence: 98%